Peningkatan Daya Saing UMKM Mimi Roti melalui Penerapan Teknologi Pengemasan dan Pemasaran Digital: Increasing the Competitiveness of Mimi Roti MSMEs through the Application of Digital Marketing and Packaging Technology - Sofi’i, Yepy Komaril; Sudarman, Sudarman; Nugroho, Willy Satrio (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This time, the community service program partner is Mimi Roti Micro, Small and Medium Enterprises (MSMEs) in Watugede, Singosari, Malang Regency. Founded in 1999, Mimi Roti MSME has experienced rapid development by reaching a production capacity of 100 donuts and burgers per day. However, Mrs. Alfiyah, as the owner of UMKM Mimi Roti, experienced significant obstacles in terms of product packaging. Using simple plastic clips causes the bread's shelf life to be only three days, limiting the growth potential and competitiveness of Mimi Roti MSMEs in the market. This service activity aims to help Mimi Roti MSMEs overcome packaging problems and increase their competitiveness in the market. To overcome this problem, the community service team took several steps, namely: analysis of partner needs, research on continuous band sealer (CBS) machines, selection and procurement of CBS machines, packaging redesign, training on using CBS machines, training on digital marketing strategies, monitoring, and evaluation. Applying the CBS machine and packaging redesign increased the shelf life of bread to 7 days, improved the quality and attractiveness of the packaging, and increased sales by up to 20%. Community service activities at MSME Mimi Roti have succeeded in helping MSME Mimi Roti overcome packaging problems, increase competitiveness, and expand its market reach. Implementing better packaging technology, attractive packaging redesign, and effective digital marketing strategies have proven to positively impact product quality, sales, and profits of Mimi Roti MSMEs.